Welding material, welding material, application and preparation method
By adding multiple elements to the welding materials and combining the fast cooling and speed characteristics of the welding molten pool, the problem that the existing welding wire system cannot meet the welding needs of high-performance aluminum alloys is solved, and the strength and service performance of the welds are effectively strengthened.
Patent Information
- Application Number
- CN202411821776.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-12-11
AI Technical Summary
The existing wire system cannot meet the welding needs of high-performance aluminum alloys, especially in terms of strength and toughness.
By adding multiple element elements, such as Si, Mg, Zn, Cu, Mn, Cr, Ti, Zr, Sc, etc. to the welding material, and combining the fast cooling characteristics of the welding molten pool, we will break through the single element alloying system of aluminum alloy wires, combined with the fast cooling and speed of the welding pool, and the aluminum alloying system is the same. , improve the lattice distortion of α-Al in the weld and the precipitation rate of nanoscale precipitation phase.
It realizes low-cost and efficient strengthening of high-performance aluminum alloy welds, improves the strength and service performance of the welds, and can be suitable for welding of high-strength aluminum alloys.
Smart Images

Figure CN119457563A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of aluminum alloy metal material welding, and in particular relates to a welding material, welding material, application and preparation method. Background Art
[0002] Aluminum alloy has the advantages of light weight, high specific strength, good formability and corrosion resistance, which helps to reduce energy consumption and pollution emissions, making it a key material for lightweighting in the transportation industry. The rapid development of aluminum alloy application trends has posed a challenge to the reliability of the connection of aluminum alloy parts in the car body.
[0003] However, the existing welding wire system is a single alloying system, such as Al-Si system (CN201910414172.6, CN202110629191.8, CN201810532500.8), Al-Mg system (CN201910114083.X, CN202211335599.5, CN201310700919.7), etc., which can only be used for welding low-strength aluminum alloys, such as 6063, 6061, 7003, 7039, etc. However, with the large-scale application of high-performance aluminum alloys, the existing welding wire can no longer meet its application requirements. The main reason for the softening of high-strength heat-treatable aluminum alloy melt welding is that the nano-scale precipitation phase in the original parent material structure at the weld is remelted to form a cast structure during welding, thereby eliminating the strengthening effect. For example, patent CN202310445098.0 discloses a new type of A1-Si welding wire, which improves weld toughness by adding Ti and Zr elements to refine the structure, but cannot make up for the reduction in strength caused by the lack of nano-scale precipitation phase. For example, patent CN202211342824.8 discloses a new type of A1-Mg welding wire, which hinders the excessive growth and aggregation of Mg2Si phase by adding Sr elements, and reduces the harm of Mg2Si to the material structure and performance. However, this patent only refines the Mg2Si phase, and after refinement, it still belongs to the micron level, and the strength cannot reach the strengthening advantage of the nano phase.
[0004] Therefore, in response to the above technical problems, it is necessary to provide a welding material, welding material, application and preparation method.
[0005] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention and should not be regarded as an acknowledgment or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art. Summary of the invention
[0006] The object of the present invention is to provide a welding material, welding material, application and preparation method.
[0007] In order to achieve the above object, a technical solution provided by a specific embodiment of the present invention is as follows:
[0008] The welding material, whose raw material composition includes, wt%: Si: 1-3%, Mg: 1.2-3.2%, Zn: 1-3.6%, Cu: 0.6-1.6%, Mn: 0.5-0.8%, Cr: 0.2-0.45%, Ti: 0.1-0.25%, Zr: 0-0.1%, Sc: 0-0.1%, Fe<0.2%, and the balance is Al and inevitable impurities.
[0009] In one or more embodiments of the present invention, a method for preparing a welding material is characterized by comprising the following steps:
[0010] Prepare raw materials, wherein at least Si, Mn, Cr, Ti, Zr, and Sc are prepared in the form of a master alloy;
[0011] The pure aluminum and the intermediate alloy except those containing Mg, Zn and Ti are melted at 730-770°C; after being completely melted, the temperature is lowered to 710-730°C to add Mg and Zn; then the temperature is raised to 730-740°C for refining and degassing; after standing to remove impurities, the Al-Ti-B intermediate alloy is added; the melt is cooled to 690-710°C for casting to obtain qualified ingots.
[0012] In one or more embodiments of the present invention, the ingot is further subjected to a two-stage homogenization heat treatment: the first stage is heated to 400-420°C at a heating rate of 2-4°C / min and kept warm for 8-12 hours; the second stage is heated to 470-520°C at a heating rate of 2-4°C / min and kept warm for 8-12 hours.
[0013] In one or more embodiments of the present invention, the welding material at least comprises a main body, and the main body is prepared by the welding material according to claim 1.
[0014] In one or more embodiments of the present invention, the ingot is heated to 440-480° C. and then extruded to obtain a rod, and then the rod is drawn to obtain a main body.
[0015] In one or more embodiments of the present invention, the extrusion speed is regulated so that the temperature of the rod at the die outlet is controlled between 470-520°C.
[0016] In one or more embodiments of the present invention, the drawing process also includes an annealing process, and the annealing process conditions are: 390-440° C., 1-3 h.
[0017] In one or more embodiments of the present invention, welding materials are used in welding operations.
[0018] In one or more embodiments of the present invention, the welding operation is selected from: laser wire welding, laser-arc hybrid welding, non-metallic inert gas shielded arc welding and metallic inert gas shielded arc welding.
[0019] In one or more embodiments of the present invention, the welding operation also includes post-weld baking, and the process conditions meet the following requirements: 140-180° C., 30-90 min.
[0020] Compared with the prior art, the welding materials, welding materials, applications and preparation methods of the present invention, based on the fast cooling rate characteristics of the welding molten pool, break through the single element alloying system of the aluminum alloy welding wire by adding multi-component elements, and improve the lattice distortion of α-Al in the weld to obtain a higher solid solution strengthening effect. At the same time, the precipitation enthalpy of the nano-scale precipitation phase is reduced by regulating the content of Zn and Cu elements, thereby improving the bake hardening effect of the weld. The combination of solid solution strengthening and precipitation strengthening realizes low-cost and efficient strengthening of high-performance aluminum alloy welds. After welding, the baking heat during the paint baking of the vehicle body or the post-weld aging heat treatment is used to promote the rapid and uniform precipitation of the nano-scale precipitation phase in the α-Al matrix, thereby strengthening the weld structure. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0022] Figure 1 This is a hardness test diagram and an average hardness diagram of the laser welded weld and the weld after baking using the welding material of the present invention in Example 1.
[0023] Figure 2 This is a tensile property test curve diagram of the laser welding weld and the weld after baking using the welding material of the present invention in Example 1.
[0024] Figure 3 This is a hardness test diagram and an average hardness diagram of the laser welded weld and the weld after baking using the welding material of the present invention in Example 2.
[0025] Figure 4 This is a tensile property test curve diagram of the laser welding weld and the weld after baking using the welding material of the present invention in Example 2.
[0026] Figure 5 This is the hardness test graph and average hardness graph of the laser welding weld and the weld after baking using the commercial ER4043 welding wire in Comparative Example 1.
[0027] Figure 6 This is a tensile properties test curve of the laser welding weld using the commercial ER4043 welding wire in Comparative Example 1.
[0028] Figure 7 This is a tensile properties curve of the laser welding weld using welding material in comparative example 2. DETAILED DESCRIPTION
[0029] In order to enable those skilled in the art to better understand the technical solutions of the present invention, the technical solutions of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
[0030] In the present invention, 1-3% Si element is added, which can ensure that the molten pool has good fluidity during welding, inhibit crack generation, and make the welding material have a wider process window. At the same time, an appropriate amount of Si element (lower than the content of hypoeutectic Al-Si welding wire) avoids the problem of too fast solidification of the molten pool, inability to discharge dissolved hydrogen, and excessively high porosity of the weld.
[0031] (2) In the present invention, 1.2-3.2% of Mg element is added, and the Mg element is dissolved in the α-Al matrix, which has a better solid solution strengthening effect than other elements. During baking, the dissolved Mg element and Si element can form dispersed nano-scale atomic clusters and nano-scale β" phases to play a precipitation strengthening role. The remaining Mg element and Si element form a Mg2Si second phase to play a certain strengthening role.
[0032] (3) In the present invention, 0.6-1.6% of Cu element is added and dissolved in the α-Al matrix to increase the solid solution strengthening effect. During baking, Cu element combines with Mg and Si elements to precipitate into dispersed nano-scale atomic clusters and nano-scale Q" / Q' strengthening phases.
[0033] (4) In the present invention, 1-3.6% Zn element is added. The important thing is that the Zn element is dissolved in the α-Al matrix, which can reduce the precipitation enthalpy of nano-scale atomic clusters and precipitated phases during baking, and can increase their precipitation rate and precipitation amount under short-term and low-temperature baking conditions.
[0034] (5) The addition of trace elements such as Mn, Cr, Ti, Zr, and Sc can improve the composition of the second phase in the structure and refine the grains. In addition, Zr and Sc elements can improve the crack sensitivity of alloys with Zn content greater than 2% during welding. The addition of trace elements not only further improves the structure performance, but also widens the welding process window.
[0035] The welding material provided by the present invention comprises the following steps:
[0036] Step 1, preparing raw materials according to the above-mentioned component ratio requirements, wherein the Al, Mg, and Zn elements in the raw materials are prepared in the form of high-purity metals, and Si, Mn, Cr, Ti, Zr, and Sc are prepared in the form of intermediate alloys.
[0037] Step 2, placing metals other than Mg, Zn and Ti in a smelting furnace, and controlling the temperature in the furnace at 730-770°C during the metal melting stage; after complete melting, lowering the temperature of the melt to 710-730°C, adding Mg and Zn to avoid burning of magnesium and zinc elements; then raising the temperature to 720-740°C for refining and degassing; after standing and removing impurities, measuring the hydrogen content of the melt, and when the content is lower than 0.18ppm, adding Al-Ti-B master alloy to refine the ingot structure; cooling the melt to 690-710°C for pouring; after pouring, removing defective parts at both ends of the ingot.
[0038] Step 3, subjecting the ingot to a two-stage homogenization heat treatment, with the first stage heating the temperature to 400-420°C at a heating rate of 2-4°C / min and keeping it warm for 8-12h, and the second stage heating the temperature to 470-520°C at a heating rate of 2-4°C / min and keeping it warm for 8-12h.
[0039] Step 4: Heat the ingot to 440-480°C before extrusion, and adjust the extrusion speed so that the temperature of the rod at the die outlet is controlled between 470-520°C to ensure the surface quality of the rod. The diameter of the extruded rod is 7-12mm.
[0040] Step 5: The rod is drawn through 10-22 passes to obtain a welding wire with a diameter of 0.8-3.0 mm. The intermediate annealing process used in the drawing process is 390-440° C., 1-3 hours, and the number of annealing times is 1-4 times.
[0041] Step 6: After the wire is drawn, the surface is physically scraped with a scraping thickness of 20-60 μm, or a chemical cleaning method such as degreasing, alkali washing, pure water washing, and drying is used to remove surface impurities.
[0042] The welding material provided by the present invention is particularly suitable for welding high-strength heat-treatable aluminum alloy materials with a strength higher than 350 MPa, thereby improving the weld strength and service performance of such alloys.
[0043] The welding material provided by the present invention is suitable for various welding methods such as laser wire welding, laser-arc composite welding, non-melting inert gas shielded arc welding and melting inert gas shielded arc welding.
[0044] The welding material provided by the present invention is suitable for laser wire welding and laser-arc composite welding. The contents of Mg, Si, Zn and Cu elements in the weld after welding must reach the following content by mass percentage: Si: 1-2%, Mg: 1-2.2%, Zn: 0.8-3% and Cu: 0.5-3%.
[0045] The welding material provided by the present invention is applicable to non-melting inert gas shielded arc welding and melting inert gas shielded arc welding. The contents of Mg, Si, Zn and Cu elements in the weld after welding shall reach the following content in terms of mass percentage: Si: 1.2-2%, Mg: 1.2-2.2%, Zn: 1-3% and Cu: 0.6-3%.
[0046] The calculation method for the content of Mg, Si, Zn and Cu elements in the weld of the welding material provided by the present invention after welding is: P=P1×S1+P2×S2.
[0047] Where P is the mass percentage of the calculated element in the weld, P1 is the mass percentage of the calculated element in the parent material, P2 is the mass percentage of the calculated element in the welding wire, S1 is the percentage of the parent material melting area to the molten pool area in the weld cross-sectional morphology, S2 is the percentage of the welding wire filling area to the molten pool area in the weld cross-sectional morphology, that is, S 1+ S2=1.
[0048] The baking strengthening method of welding materials provided by the present invention is to heat the weld seam with heating gas during the body painting production process or the post-weld aging heat treatment process. The painting baking or aging heat treatment temperature range is between 140-180°C and the time is between 30-90 minutes. In this process, a large number of nano-scale atomic clusters and precipitated phases are precipitated in the weld seam structure, thereby further improving the weld seam strength.
[0049] Embodiment 1:
[0050] The welding material of this embodiment includes, by mass percentage, the following components: Si: 1.5%, Mg: 1.6%, Zn: 2.5%, Cu: 0.75%, Mn: 0.6%, Cr: 0.3%, Ti: 0.2%, Fe: 0.1%, and the remainder is Al and unavoidable impurities.
[0051] The preparation method comprises the following steps:
[0052] Step 1: Prepare the raw materials according to the set composition ratio. The Al, Mg, and Zn elements in the raw materials are prepared in the form of 99.9% high-purity metals, and Si, Mn, Cr, and Ti are prepared in the form of Al-20% Si, Al-10% Mn, Al-10% Cr, and Al-5% Ti-1% B master alloys. After the casting is completed, remove the defective parts at both ends of the ingot.
[0053] Step 3, subjecting the ingot to a two-stage homogenization heat treatment, with the first stage heating the temperature to 400°C at a heating rate of 3°C / min and keeping it warm for 8 hours, and the second stage heating the temperature to 480°C at a heating rate of 2°C / min and keeping it warm for 10 hours.
[0054] In order to obtain a welding wire of a certain specification, the following further processing can be performed:
[0055] Step 4: Heat the ingot to 450°C before extrusion, adjust the extrusion speed so that the temperature of the rod at the die outlet is controlled between 480-490°C, and the diameter of the extruded rod is 9.5 mm.
[0056] Step 5: After the bar is annealed at 410°C for 3h, it is drawn 14 times, and annealing is required three times during the drawing process. After the wire is drawn, the surface is physically scraped to obtain a wire with a diameter of 1.2mm.
[0057] The above welding wire is used to perform laser wire welding on a 370MPa grade high-strength 6XXX aluminum alloy T5 state plate, the plate thickness is 2.5mm, and its specific composition mass fraction is Si: 1%, Mg: 0.8%, Cu: 0.5%, Mn: 0.5%, Cr: 0.21%, Ti: 0.05%, Fe < 0.15%, and the balance is Al.
[0058] The process parameters of laser welding are as follows: laser power 2400 W, welding speed 40 mm / s, laser beam circular swing, swing amplitude 1.5 mm, swing frequency 200 Hz, wire feeding speed 6 m / min.
[0059] After welding, the contents of Mg, Si, Zn and Cu elements in the weld were calculated. Through metallographic observation of the weld cross section, it was measured that S1 and S2 were 60% and 40% respectively. The formula P = P1×S1+P2×S2 was used to calculate that Mg: 1.15%, Si: 1.2%, Zn: 1%, and Cu: 0.6%.
[0060] Embodiment 2:
[0061] The welding material of this embodiment includes, by mass percentage, the following components: Si: 1.2%, Mg: 2.8%, Zn: 2%, Cu: 0.6%, Mn: 0.6%, Cr: 0.25%, Ti: 0.15%, Fe: 0.1%, and the remainder is Al and unavoidable impurities.
[0062] The preparation method comprises the following steps:
[0063] Step 1: Prepare the raw materials according to the set chemical composition ratio of the welding wire. The Al, Mg, and Zn elements in the raw materials are prepared in the form of 99.9% high-purity metals, and Si, Mn, Cr, and Ti are prepared in the form of Al-20% Si, Al-10% Mn, Al-10% Cr, and Al-5% Ti-1% B master alloys. After the casting is completed, remove the defective parts at both ends of the ingot.
[0064] Step 3, subjecting the ingot to a two-stage homogenization heat treatment, with the first stage heating the temperature to 400°C at a heating rate of 3°C / min and keeping it warm for 8 hours, and the second stage heating the temperature to 480°C at a heating rate of 3°C / min and keeping it warm for 10 hours.
[0065] In order to obtain a welding wire of a certain specification, the following further processing can be performed:
[0066] Step 4: Heat the ingot to 460°C before extrusion, adjust the extrusion speed so that the temperature of the rod at the die outlet is controlled between 480-500°C, and the diameter of the extruded rod is 9.5 mm.
[0067] Step 5: After the bar is annealed at 400°C for 3h, it is drawn 12 times, and annealing is required three times during the drawing process. After the wire is drawn, the surface is physically scraped to obtain a wire with a diameter of 1.2mm.
[0068] The above welding wire is used to perform laser wire welding on 400MPa grade high-strength and tough 6XXX aluminum alloy T5 state plates, and the plate thickness is 2.5mm. Its specific composition is Si: 1.2%, Mg: 0.95%, Zn: 0.2%, Cu: 0.6%, Mn: 0.65%, Cr: 0.25%, Ti: 0.05%, Fe < 0.15%, and the balance is Al.
[0069] The process parameters of laser welding are as follows: laser power 2400 W, welding speed 40 mm / s, laser beam circular swing, swing amplitude 1.6 mm, swing frequency 200 Hz, wire feeding speed 6 m / min.
[0070] After welding, the contents of Mg, Si, Zn and Cu elements in the weld were calculated. Through metallographic observation of the weld cross section, it was measured that S1 and S2 were 55% and 45% respectively. The formula P = P1×S1+P2×S2 was used to calculate that Mg: 1.8%, Si: 1.2%, Zn: 1%, Cu: 0.6%.
[0071] Example 3
[0072] The only difference between this embodiment and Embodiment 1 is that the raw material composition of the welding material includes, by weight percent: Si: 1.5%, Mg: 1.6%, Zn: 2.5%, Cu: 0.75%, Mn: 0.6%, Cr: 0.3%, Ti: 0.2%, Sc: 0.05%, Fe: 0.1%, and the balance is Al and unavoidable impurities.
[0073] Example 4
[0074] The only difference between this embodiment and Embodiment 1 is that the raw material composition of the welding material includes, by weight percent: Si: 1.5%, Mg: 1.6%, Zn: 2.5%, Cu: 0.75%, Mn: 0.6%, Cr: 0.3%, Ti: 0.2%, Zr: 0.05%, Fe: 0.1%, and the balance is Al and unavoidable impurities.
[0075] Example 5
[0076] The only difference between this embodiment and Embodiment 1 is that the raw material composition of the welding material includes, by weight percent: Si: 1%, Mg: 1.2%, Zn: 1%, Cu: 1%, Mn: 0.5%, Cr: 0.2%, Ti: 0.1%, Zr: 0.1%, Sc: 0.1%, Fe0.15%, and the balance is Al and unavoidable impurities.
[0077] Example 6
[0078] The only difference between this embodiment and Embodiment 1 is that the raw material composition of the welding material includes, by weight percent: Si: 3%, Mg: 3.2%, Zn: 3.6%, Cu: 1.6%, Mn: 0.8%, Cr: 0.45%, Ti: 0.25%, Zr: 0.1%, Sc: 0.1%, Fe0.05%, and the balance is Al and unavoidable impurities.
[0079] Example 7
[0080] The difference between this embodiment and embodiment 1 is that pure aluminum and master alloy other than those containing Mg, Zn and Ti are smelted at 730-770°C; after being completely melted, the temperature is lowered to 710-730°C to add Mg and Zn; the temperature is then raised to 730-740°C for refining and degassing; after standing to remove impurities, Al-Ti-B master alloy is added; the melt is cooled to 690-710°C for casting to obtain qualified ingots.
[0081] Example 8
[0082] The difference between this embodiment and embodiment 1 is that pure aluminum and master alloy other than those containing Mg, Zn and Ti are smelted at 730-770°C; after being completely melted, the temperature is lowered to 710-730°C to add Mg and Zn; the temperature is then raised to 730-740°C for refining and degassing; after standing to remove impurities, Al-Ti-B master alloy is added; the melt is cooled to 690-710°C for casting to obtain qualified ingots.
[0083] Example 9
[0084] The only difference between this embodiment and embodiment 1 is: two-stage homogenization heat treatment: the first stage is heated to 400-420°C at a heating rate of 2-4°C / min and kept warm for 8-12h, and the second stage is heated to 470-520°C at a heating rate of 2-4°C / min and kept warm for 8-12h.
[0085] Example 10
[0086] The only difference between this embodiment and embodiment 1 is: two-stage homogenization heat treatment: the first stage is heated to 400-420°C at a heating rate of 2-4°C / min and kept warm for 8-12h, and the second stage is heated to 470-520°C at a heating rate of 2-4°C / min and kept warm for 8-12h.
[0087] Embodiment 11
[0088] The only difference between this embodiment and embodiment 1 is: a method for preparing welding material, comprising heating an ingot to 440°C and then extruding it to obtain a rod, and then drawing the rod to obtain a welding material body, the extrusion satisfies the requirement of regulating the extrusion speed so that the temperature of the rod at the die outlet is controlled between 470-480°C, and the drawing also includes an annealing process, and the annealing process conditions are: 440°C, 1h.
[0089] Example 12
[0090] The only difference between this embodiment and embodiment 1 is: a method for preparing welding material, comprising heating an ingot to 480°C and then extruding it to obtain a rod, and then drawing the rod to obtain a welding material body, the extrusion satisfies the requirement of regulating the extrusion speed so that the temperature of the rod at the die outlet is controlled between 500-520°C, and the drawing process also includes an annealing process, and the annealing process conditions are: 390°C, 2h.
[0091] Comparative Example 1:
[0092] The commercial ER4043 aluminum alloy welding wire was used to laser weld 400MPa high-strength and tough 6XXX aluminum alloy T5 state plates with a thickness of 2mm. The specific composition of the welding wire is Si: 5.5%, Mg: 0.05%, Zn: 0.05%, Cu: 0.2%, Ti: 0.15%, Fe: 0.4%, and the balance is Al. The specific composition of the plate is Si: 1.2%, Mg: 0.95%, Zn: 0.2%, Cu: 0.6%, Mn: 0.65%, Cr: 0.25%, Ti: 0.05%, Fe < 0.15%, and the balance is Al.
[0093] The process parameters of laser welding are as follows: laser power 2100 W, welding speed 40 mm / s, laser beam circular swing, swing amplitude 1.2 mm, swing frequency 150 Hz, wire feeding speed 6 m / min.
[0094] After welding, the contents of Mg, Si, Zn and Cu elements in the weld were calculated. Through metallographic observation of the weld cross section, it was measured that S1 and S2 were 43% and 57% respectively. The formula P = P1×S1+P2×S2 was used to calculate that Mg: 0.37%, Si: 3.61%, Zn: 0.03% and Cu: 0.31%.
[0095] Comparative Example 2:
[0096] A comparative welding wire was used to laser weld 370MPa grade high strength and toughness 6XXX aluminum alloy T5 state plate, the plate thickness was 2mm. The specific composition of the welding wire is Si: 1.5%, Mg: 1.6%, Zn: 0%, Cu: 0%, Mn: 0.6%, Cr: 0.25%, Ti: 0.15%, Fe: 0.1%, and the balance is Al and inevitable impurities. The welding wire is made after multiple processes such as melting, mean heat treatment, extrusion, drawing, annealing, etc., and the diameter is 1.2mm. The specific composition of the plate is Si: 1.1%, Mg: 0.79%, Cu: 0.45%, Mn: 0.6%, Cr: 0.2%, Ti: 0.05%, Fe < 0.15%, and the balance is Al.
[0097] The process parameters of laser welding are as follows: laser power 2100 W, welding speed 40 mm / s, laser beam circular swing, swing amplitude 1.5 mm, swing frequency 200 Hz, wire feeding speed 6 m / min.
[0098] After welding, the contents of Mg, Si, Zn and Cu elements in the weld were calculated. Through metallographic observation of the weld cross section, it was measured that S1 and S2 were 51% and 49% respectively. The formula P = P1×S1+P2×S2 was used to calculate that Mg: 1.2%, Si: 1.3%, Zn: 0%, Cu: 0.2%.
[0099] Test Example 1:
[0100] Microhardness tests were performed on the welds obtained from the sample of Example 1 and the welds after baking, wherein the baking process was electrophoresis baking at 175°C for 35 minutes, primer baking at 140°C for 25 minutes, and topcoat baking at 140°C for 25 minutes, a total of three baking steps. The microhardness test results are shown in Figure 1. Figure 1 As shown. Figure 1 It can be seen that the hardness of the weld has been significantly improved after baking. The average hardness of the weld before baking is 74.8HV, and the average hardness after three-pass baking process reaches 88.1HV, and the hardness after baking is increased by 17.8%. This welding wire composition has excellent baking hardening effect.
[0101] Similarly, the tensile properties of the weld in Example 1 and the weld after baking were tested, wherein the baking process was electrophoresis baking at 175°C for 35 minutes, primer baking at 140°C for 25 minutes, and topcoat baking at 140°C for 25 minutes. The tensile test of the weld joint adopted the transverse displacement velocity method, and the tensile speed was 2 mm / min. The results are as follows: Figure 2 As shown. The tensile strength of the welds before baking was 313.7MPa and 315.9MPa respectively. After three baking processes, the welds were significantly improved, reaching 338.6MPa and 335.2MPa respectively. Test Example 2:
[0102] Microhardness tests were performed on the welds obtained from the samples of Example 2 and the welds after baking. The baking process was electrophoresis baking at 175°C for 35 minutes, primer baking at 140°C for 25 minutes, and topcoat baking at 140°C for 25 minutes. The microhardness test results are shown in Figure 2. Figure 3 The hardness of the weld after baking is significantly higher than that before baking. The average hardness of the weld before baking is 75.2HV. After three baking processes, the average hardness of the weld is increased to 90.7HV, and the bake hardening value reaches 15.5HV. The hardness of the weld is increased by 20.6% compared with that before baking.
[0103] Similarly, the tensile properties of the weld in Example 2 and the weld after baking were tested, wherein the baking process was electrophoresis baking at 175°C for 35 minutes, primer baking at 140°C for 25 minutes, and topcoat baking at 140°C for 25 minutes. The tensile test of the weld joint adopted the transverse displacement velocity method, and the tensile speed was 2 mm / min. The results are as follows: Figure 4 As shown. The tensile strength of the welds before baking was 341.0MPa and 333.1MPa respectively. After three baking processes, the welds were significantly improved, reaching 373.2MPa and 369.2MPa respectively. Test Example 3:
[0104] Microhardness tests were conducted on the welds obtained from the sample of Comparative Example 1 and the welds after baking, wherein the baking process was electrophoresis baking at 175°C for 35 minutes, primer baking at 140°C for 25 minutes, and topcoat baking at 140°C for 25 minutes, a total of three baking steps. The microhardness test results are shown in Figure 1. Figure 5 As shown in the figure, it can be seen that the hardness of the weld after baking is not significantly improved compared with that before baking. The average hardness before baking is 75.7HV, and the hardness after baking is only 77.4HV. The hardness after baking is only increased by 2.2%, which is far lower than the baking hardening improvement value of more than 15% of the present invention.
[0105] Similarly, the tensile properties of the weld after baking in Comparative Example 1 were tested. The tensile test of the weld joint was carried out using the transverse displacement velocity method with a tensile speed of 2 mm / min. The results are shown in Figure 6 The tensile strength of the welds using the commercial ER4043 welding wire only reached 277.9 MPa and 280.6 MPa, which is significantly lower than the weld strength in the embodiment.
[0106] Test Example 4:
[0107] The tensile properties of the weld obtained from the sample of comparative example 2 and the weld after baking were tested. The baking process was electrophoresis baking 175℃-35min, primer baking 140℃-25min, and topcoat baking 140℃-25min, a total of three baking steps. The tensile test of the weld joint adopted the transverse displacement velocity method, and the tensile speed was 2mm / min. The results are as follows Figure 7 The tensile strength of the welds using the welding wire of Comparative Example 2 before baking was 268.8 MPa and 262.2 MPa respectively, and the tensile strength of the welds after baking was only 270.2 MPa and 274.3 MPa, which was significantly lower than the weld strength in the embodiment.
[0108] Test Example 5:
[0109] The tensile properties of the welds obtained using the samples of Example 3 and the welds after baking were tested, wherein the baking process was electrophoresis baking 175°C-35min, primer baking 140°C-25min, and topcoat baking 140°C-25min, a total of three baking steps. The tensile test of the weld joint adopted the transverse displacement velocity method, and the tensile speed was 2mm / min. The tensile strength of the welds using the welding wire of Example 3 before baking was 318.8MPa and 316.1MPa, respectively, and the tensile strength of the welds after baking was increased to 340.2MPa and 337.1MPa.
[0110] Test Example 6:
[0111] The tensile properties of the welds obtained using the samples of Example 4 and the welds after baking were tested, wherein the baking process was electrophoresis baking 175°C-35min, primer baking 140°C-25min, and topcoat baking 140°C-25min, a total of three baking steps. The tensile test of the weld joint adopted the transverse displacement velocity method, and the tensile speed was 2mm / min. The tensile strength of the welds using the welding wire of Example 4 before baking was 314.3MPa and 310.4MPa, respectively, and the tensile strength of the welds after baking reached 337.6MPa and 332.7MPa.
[0112] Test Example 7:
[0113] The tensile properties of the welds obtained using the sample of Example 5 and the welds after baking were tested, wherein the baking process was electrophoresis baking 175°C-35min, primer baking 140°C-25min, and topcoat baking 140°C-25min, a total of three baking steps. The tensile test of the weld joint adopted the transverse displacement velocity method, and the tensile speed was 2mm / min. The tensile strength of the welds using the welding wire of Example 5 before baking was 308.9MPa and 306.1MPa, respectively, and the tensile strength of the welds after baking reached 321.8MPa and 326.9MPa.
[0114] Test Example 8:
[0115] The tensile properties of the welds obtained using the samples of Example 6 and the welds after baking were tested, wherein the baking process was electrophoresis baking 175°C-35min, primer baking 140°C-25min, and topcoat baking 140°C-25min, a total of three baking steps. The tensile test of the weld joint adopted the transverse displacement velocity method, and the tensile speed was 2mm / min. The tensile strength of the welds using the welding wire of Example 6 before baking was 339.9MPa and 336.4MPa, respectively, and the tensile strength of the welds after baking was increased to 374.2MPa and 379.1MPa.
[0116] Test Example 9:
[0117] The tensile properties of the welds obtained using the samples of Example 7 and the welds after baking were tested, wherein the baking process was electrophoresis baking 175°C-35min, primer baking 140°C-25min, and topcoat baking 140°C-25min, a total of three baking steps. The tensile test of the weld joint adopted the transverse displacement velocity method, and the tensile speed was 2mm / min. The tensile strength of the welds using the welding wire of Example 7 before baking was 309.4MPa and 316.3MPa, respectively, and the tensile strength of the welds after baking was increased to 334.6MPa and 339.2MPa.
[0118] Test Example 10:
[0119] The tensile properties of the welds obtained using the samples of Example 8 and the welds after baking were tested, wherein the baking process was electrophoresis baking 175°C-35min, primer baking 140°C-25min, and topcoat baking 140°C-25min, a total of three baking steps. The tensile test of the weld joint adopted the transverse displacement velocity method, and the tensile speed was 2mm / min. The tensile strength of the welds using the welding wire of Example 8 before baking was 310.4MPa and 315.2MPa, respectively, and the tensile strength of the welds after baking reached 332.2MPa and 329.8MPa.
[0120] Test Example 11:
[0121] The tensile properties of the welds obtained using the sample of Example 9 and the welds after baking were tested, wherein the baking process was electrophoresis baking 175°C-35min, primer baking 140°C-25min, and topcoat baking 140°C-25min, a total of three baking steps. The tensile test of the weld joint adopted the transverse displacement velocity method, and the tensile speed was 2mm / min. The tensile strength of the welds using the welding wire of Example 9 before baking was 319.7MPa and 325.4MPa, respectively, and the tensile strength of the welds after baking was increased to 334.7MPa and 336.3MPa.
[0122] Test Example 12:
[0123] The tensile properties of the welds obtained using the sample of Example 10 and the welds after baking were tested, wherein the baking process was electrophoresis baking 175°C-35min, primer baking 140°C-25min, and topcoat baking 140°C-25min, a total of three baking steps. The tensile test of the weld joint adopted the transverse displacement velocity method, and the tensile speed was 2mm / min. The tensile strength of the welds using the welding wire of Example 10 before baking was 323.1MPa and 317.3MPa, respectively, and the tensile strength of the welds after baking was increased to 338.2MPa and 329.1MPa.
[0124] Test Example 13:
[0125] The tensile properties of the welds obtained using the sample of Example 11 and the welds after baking were tested, wherein the baking process was electrophoresis baking 175°C-35min, primer baking 140°C-25min, and topcoat baking 140°C-25min, a total of three baking steps. The tensile test of the weld joint adopted the transverse displacement velocity method, and the tensile speed was 2mm / min. The tensile strength of the welds using the welding wire of Example 11 before baking was 309.8MPa and 316.1MPa, respectively, and the tensile strength of the welds after baking was increased to 333.2MPa and 328.5MPa.
[0126] Test Example 14:
[0127] The tensile properties of the welds obtained using the sample of Example 12 and the welds after baking were tested, wherein the baking process was electrophoresis baking 175°C-35min, primer baking 140°C-25min, and topcoat baking 140°C-25min, a total of three baking steps. The tensile test of the weld joint adopted the transverse displacement velocity method, and the tensile speed was 2mm / min. The tensile strength of the welds using the welding wire of Example 12 before baking was 311.2MPa and 316.9MPa, respectively, and the tensile strength of the welds after baking was increased to 337.1MPa and 329.7MPa.
[0128] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
[0129] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A welding material, whose raw material composition includes, by weight percent: Si: 1-3%, Mg: 1.2-3.2%, Zn: 1-3.6%, Cu: 0.6-1.6%, Mn: 0.5-0.8%, Cr: 0.2-0.45%, Ti: 0.1-0.25%, Zr: 0-0.1%, Sc: 0-0.1%, Fe<0.2%, and the balance is Al and unavoidable impurities.
2. The method for preparing the welding material according to claim 1, characterized in that: The steps include: Prepare raw materials, wherein at least Si, Mn, Cr, Ti, Zr, and Sc are prepared in the form of a master alloy; The pure aluminum and the intermediate alloy except those containing Mg, Zn and Ti are melted at 730-770°C; after being completely melted, the temperature is lowered to 710-730°C to add Mg and Zn; then the temperature is raised to 730-740°C for refining and degassing; after standing to remove impurities, the Al-Ti-B intermediate alloy is added; the melt is cooled to 690-710°C for casting to obtain qualified ingots.
3. The method for preparing the welding material according to claim 2, characterized in that: The method also includes subjecting the ingot to a two-stage homogenization heat treatment: the first stage is to heat the temperature to 400-420°C at a heating rate of 2-4°C / min and keep the temperature for 8-12 hours; the second stage is to heat the temperature to 470-520°C at a heating rate of 2-4°C / min and keep the temperature for 8-12 hours.
4. A welding material, comprising at least a main body, wherein the main body is prepared by the welding material according to claim 1.
5. The method for preparing welding material according to claim 4, characterized in that: The method comprises heating the ingot to 440-480° C. and then extruding the ingot to obtain a rod, and then drawing the rod to obtain a main body.
6. The method for preparing welding material according to claim 5, characterized in that: The extrusion is performed to adjust the extrusion speed so that the temperature of the rod at the die outlet is controlled between 470-520°C.
7. The method for preparing welding material according to claim 5, characterized in that: The drawing process also includes an annealing process, and the annealing process conditions are: 390-440° C., 1-3 hours.
8. Use of the welding material according to claim 4 in welding operations.
9. The use according to claim 8, characterized in that: The welding operation is selected from: laser wire welding, laser-arc hybrid welding, non-metallic inert gas shielded arc welding and metallic inert gas shielded arc welding.
10. The use according to claim 9, characterized in that: The welding operation also includes post-weld baking, and the process conditions meet the following requirements: 140-180° C., 30-90 min.
Citation Information
Patent Citations
Ultra-fine grain aluminum alloy gold welding wire and preparation method thereof
CN104722945A
Manufacturing method for silicon-contained aluminum alloy welding wire rod for spaceflight
CN108531788A
High-magnesium-manganese-chromium-cobalt-aluminum alloy for manufacturing welding wire and its preparation method
CN109732239B
Composite reinforced Al-Si alloy welding wire and preparation method thereof
CN110172619A
Welding wire for die-casting aluminum alloy and preparation method of welding wire
CN113385854A
Cited By
Aluminum alloy welding material and high-toughness welding seam preparation method
CN120206090A
Filling material for 6XXX series aluminum alloy and welding process of filling material
CN120206091A
High-iron-content aluminum alloy welding wire and preparation method and application thereof
CN122058086A